2017
DOI: 10.2217/imt-2017-0096
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Treatment with Intratumoral Electroporation of Tavokinogene Telseplasmid (pIL-12, Tavokinogene Telseplasmid)

Abstract: Tumors evade detection and/or clearance by the immune system via multiple mechanisms. IL-12 is a potent immunomodulatory cytokine that plays a central role in immune priming. However, systemic delivery of IL-12 can result in life-threatening toxicity and therefore has shown limited efficacy at doses that can be safely administered. We developed an electroporation technique to produce highly localized IL-12 expression within tumors leading to regression of both treated and untreated lesions in animal models and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
(62 reference statements)
0
34
0
Order By: Relevance
“… 5 Subsequently, cytokine fusion proteins and plasmids expressing cytokines have been developed with the aim of increasing efficacy. 75 , 76 For example, the immunocytokine fusion protein L19–IL-2 (Darleukin) is a targeted form of IL-2 that recognises the extra domain B of fibronectin, which is expressed in cancer-associated blood vessels and extracellular matrix but absent from almost all healthy tissue. 75 In a single-arm Phase 2 trial, L19–IL-2 resulted in local responses, including local complete responses.…”
Section: Novel Agents In Development For Unresectable and Metastatic mentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Subsequently, cytokine fusion proteins and plasmids expressing cytokines have been developed with the aim of increasing efficacy. 75 , 76 For example, the immunocytokine fusion protein L19–IL-2 (Darleukin) is a targeted form of IL-2 that recognises the extra domain B of fibronectin, which is expressed in cancer-associated blood vessels and extracellular matrix but absent from almost all healthy tissue. 75 In a single-arm Phase 2 trial, L19–IL-2 resulted in local responses, including local complete responses.…”
Section: Novel Agents In Development For Unresectable and Metastatic mentioning
confidence: 99%
“…78 Tavokinogene telseplasmid was given orphan drug status by the US Food and Drug Administration (FDA) in 2017 for the treatment of unresectable metastatic melanoma. 76 …”
Section: Novel Agents In Development For Unresectable and Metastatic mentioning
confidence: 99%
“…Therefore, combination therapy of IL-2 and rituximab could benefit patients with refractory NHL. In patients with melanoma given a combination of IL-12 and PD-1-targeted therapy in a 24-week treatment cycle, the disease control rate reached 59%, and 41% (9/22) of patients had a CR [ 19 ]. IL-12 greatly reduced the incidence of adverse reactions caused by the administration of the anti-PD-1 antibody alone, and it potentiated the activity of PD-1 antibodies without increasing significant toxicity [ 19 ].…”
Section: Progress In Therapeutic Strategies Of Il-12 Treatment For Camentioning
confidence: 99%
“… 9 10 In preclinical models, IL-12 has consistently been shown to reduce tumor burden and increase survival though early clinical trials revealed IL-12-driven systemic toxicities. 11 Recent clinical studies; however, demonstrate that locally-delivered IL-12 is well-tolerated in high-grade glioma 12 and metastatic melanoma, 13 14 suggesting that methods to deliver IL-12 to the TME could harness the preclinical successes for use in humans.…”
Section: Introductionmentioning
confidence: 99%